Landscape analysis for multi-hazard prevention in Orco and Soana valleys, North-Western Italy - Turconi,L; Tropeano,D; Savio,G; Kumar,De S; Mason,PJ (Natural Hazards and Earth System Sciences Discussions, 2015)
A Civil Protection Plan has been drafted for a 600 km2 mountainous region in NWItaly Consisting of Orco and Soana Valleys. It is a part of the oldest natural park inItaly and attracts several thousand tourists every year. The work is concerned with the analysis of relevant physiographic characteristics of this Alpine landscapehavingextremely variable geomorphology and possess a long history of instability. Thousandsof records as well as digital maps (involving overlay and comparison of up to 90 GISlayers) have been analyzed and cross-correlated to find out the details of the events.The study area experienced different types of natural hazards, typical of the whole Alpine environment. Thus, the present area has been selected for such multi-hazardresearch in which several natural processes have been investigated, concerning theirdamaging effects over the land. Due to 36 different severe hazardous events at least250 deaths have been recorded in the area since 18th Century, in the occasion of.